Contribution of Cytokines to Tissue Damage During Human Respiratory Syncytial Virus Infection - Bohmwald, Karen; Gálvez, Nicolás M. S.; Canedo-Marroquín, Gisela; Pizarro-Ortega, Magdalena S.; Andrade-Parra, Catalina; Gómez-Santander, Felipe; Kalergis, Alexis M. (Frontiers in Immunology, 2019)
The human respiratory syncytial virus (hRSV) remains one of the leading pathogens causing acute respiratory tract infections (ARTIs) in children younger than two years old, worldwide. Hospitalizations during the winter season due to hRSV-induced bronchiolitis and pneumonia increase every year. Despite this, there are no available vaccines to mitigate the health and economic burden caused by hRSV infection. The pathology caused by hRSV induces significant damage to the pulmonary epithelium, due to an excessive inflammatory response at the airways. Cytokines are considered essential players for the establishment and modulation of the immune and inflammatory responses, which can either be beneficial or harmful for the host. The deleterious effect observed upon hRSV infection is mainly due to tissue damage caused by immune cells recruited to the site of infection. This cellular recruitment takes place due to an altered profile of cytokines secreted by epithelial cells. As a result of inflammatory cell recruitment, the amounts of cytokines, such as IL-1, IL-6, IL-10, and CCL5 are further increased, while IL-10 and IFN- are decreased. However, additional studies are required to elicit the mediators directly associated with hRSV damage entirely. In addition to the detrimental induction of inflammatory mediators in the respiratory tract caused by hRSV, reports indicating alterations in the central nervous system have been published. Indeed, elevated levels of IL-6, IL-8 (CXCL8), CCL2, and CCL4 have been reported in cerebrospinal fluid from patients with severe bronchiolitis and hRSV-associated encephalopathy. In this review article, we provide an in-depth analysis of the role of cytokines secreted upon hRSV infection and their potentially harmful contribution to tissue damage of the respiratory tract and the central nervous system.